A sandwich structure flexible piezoelectric composite film and its preparation method and application

By adopting a flexible piezoelectric composite film with a sandwich structure, the combination of dopamine-modified inorganic piezoelectric nanoparticles and polymer film layer is solved, and the defects of existing ferroelectric ceramic materials when the strain is greater than 4%, achieving a combination of high-voltage electrical properties and flexible characteristics, and is suitable for a variety of electronic equipment and sensing applications.

CN114824056BActive Publication Date: 2025-04-08ZHEJIANG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210254125.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-15
Publication Date
2025-04-08
Estimated Expiration
2042-03-15

AI Technical Summary

Technical Problem

Existing ferroelectric ceramic materials are prone to internal defects and fractures when the strain is greater than 4%, which limits their flexible application and makes it difficult to achieve high-voltage electrical performance and flexibility characteristics at the same time.

Method used

A flexible piezoelectric composite film with a sandwich structure is used to form a composite film with excellent flexibility and high voltage electrical properties through the combination of inorganic piezoelectric nanoparticles modified with dopamine surface and a polymer film layer.

Benefits of technology

It realizes high-quality flexible piezoelectric film preparation, has high voltage electrical coefficient and ferroelectric properties, and avoids the problem of hardness and fragility of materials. It is suitable for wearable electronic devices and flexible sensing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824056B_ABST
    Figure CN114824056B_ABST
Patent Text Reader

Abstract

The present invention discloses a sandwich-structured flexible piezoelectric composite film, which has a sandwich structure, wherein the upper and lower layers are composed of inorganic piezoelectric nanoparticles modified with dopamine, and the middle layer is a polymer film layer. The present invention also discloses a method for preparing the composite film: dispersing the inorganic piezoelectric nanoparticles modified with dopamine in an ethanol solution to obtain a suspension; placing the polymer film at the bottom of a beaker, pouring the suspension, and waiting for the nanoparticles to naturally settle to one surface of the polymer film; performing heat treatment to obtain an inorganic nanoparticle layer / polymer film layer with a double-layer structure; placing the film at the bottom of the beaker again, with the polymer film layer facing upward, pouring the suspension, and waiting for the nanoparticles to naturally settle to the other surface of the polymer film; performing heat treatment to obtain a sandwich-structured flexible piezoelectric composite film. The composite film prepared by the present invention has good piezoelectric and ferroelectric properties and excellent flexibility, and can be used in the field of wearable electronic devices or flexible sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of organic-inorganic composite piezoelectric films, and in particular relates to a sandwich-structured flexible piezoelectric composite film and a preparation method and application thereof. Background Art

[0002] In the context of the rapid development of the electronic information industry and the rapid maturity of the Internet of Things technology in the current intelligent era, the development of the flexible electronics industry and related technologies has become an inevitable trend. In recent years, the development of flexible electronic devices has also put forward new requirements for the flexibility of piezoelectric films. For example, the application of ABO3-type perovskite oxide piezoelectric materials is usually concentrated on ceramics and single crystal materials, and its films are mostly grown on rigid oxide substrates, which cannot achieve mechanical deformation in the form of bending, and achieve the purpose of elastic sensing and energy collection. For example, the one-dimensional metal-doped perovskite-type niobate piezoelectric material and its preparation method and flexible piezoelectric film and its application disclosed in the Chinese patent with publication number CN109942022A, and a fully organic metal-free perovskite cement-based piezoelectric material, preparation method and application disclosed in the Chinese patent with publication number CN111646745A. More importantly, most ferroelectric single crystals and ceramic materials will cause the generation and development of internal defects when the strain is greater than 4%, resulting in fracture failure, which greatly limits their flexible application.

[0003] Therefore, how to prepare high-quality flexible piezoelectric films so that they can maintain the high polarization strength, high piezoelectric coefficient and temperature stability of ferroelectric ceramics, while avoiding their shortcomings of being hard and fragile and achieving flexibility, thereby meeting the requirements of wearable miniaturized devices, has become a hot topic in current research.

[0004] The purpose of this study is to find a simple method for preparing a sandwich-structured flexible piezoelectric composite film to obtain a composite film that has both flexibility and high piezoelectric properties, so that this type of material has a broader application prospect. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a sandwich-structured flexible piezoelectric composite film. The prepared sandwich-structured flexible piezoelectric composite film has good piezoelectric and ferroelectric properties and excellent flexibility, and can be applied in wearable electronic devices or flexible sensing fields.

[0006] The present invention provides the following technical solutions:

[0007] A sandwich-structured flexible piezoelectric composite film has a sandwich structure, wherein the upper and lower layers are composed of inorganic piezoelectric nanoparticles modified with dopamine surfaces, and the middle layer is a polymer film layer.

[0008] The mass ratio of the inorganic piezoelectric nanoparticles modified with dopamine on the surface in the upper layer or the lower layer to the polymer in the polymer film layer is 1:(1-10), and the thickness of the composite film is 10-100 μm.

[0009] Preferably, the thickness of the composite film is 50-60 μm.

[0010] The inorganic piezoelectric nanoparticles are selected from barium titanate (BTO), potassium sodium niobate (KNN) or lead zirconate titanate (PZT) nanoparticles, and have a size of 10 to 100 nm.

[0011] The material of the polymer film layer is selected from PVDF, P (VDF-TrFE), P (VDF-TrFE-CTFE) or PDMS.

[0012] The present invention also provides a method for preparing a sandwich structure flexible piezoelectric composite film, the preparation method comprising the following steps:

[0013] (1) dispersing dopamine-modified inorganic piezoelectric nanoparticles in an ethanol solution to obtain a suspension;

[0014] (2) placing a polymer film at the bottom of a beaker, pouring the suspension prepared in step (1) into the beaker, and allowing the suspension to stand until the nanoparticles naturally settle to a surface of the polymer film, thereby obtaining a nanoparticle layer;

[0015] (3) heat-treating the polymer film of step (2) to obtain an inorganic nanoparticle layer / polymer film layer having a double-layer structure;

[0016] (4) placing the inorganic nanoparticle layer / polymer film layer having a double-layer structure in step (3) at the bottom of a beaker with the polymer film layer facing upward, pouring the suspension in step (1) into the beaker and allowing the suspension to stand until the nanoparticles naturally settle to the other surface of the polymer film, thereby obtaining a nanoparticle layer;

[0017] (5) Heat-treating the polymer film of step (4) to obtain a flexible piezoelectric composite film with a sandwich structure.

[0018] Preferably, the polymer film is prepared by casting or spin coating and has a thickness of 10 to 60 μm.

[0019] Preferably, the concentration of the suspension is 1 to 200 mg / mL.

[0020] Preferably, in steps (3) and (5), the heat treatment temperature is 150-200° C. and the time is 2-3 hours.

[0021] The present invention also provides an application of the above-mentioned sandwich structure flexible piezoelectric composite film in the field of wearable electronic devices or flexible sensing.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The components of the present invention are simple, and the selected raw materials are all commercial products.

[0024] (2) The preparation process of the present invention is simple, the process is easy to control, the experimental repeatability is high, and the cost is low.

[0025] (3) Piezoelectric coefficient of the sandwich structure composite film in the present invention |d 33 |~14pC / N, which is about 2.8 times that of pure PVDF (~5pC / N); it is twice that of the mixed equal amount of piezoelectric nanoparticles 0-3 type composite film (~7pC / N).

[0026] (4) The ferroelectric properties of the sandwich structure composite film of the present invention are significantly improved compared with pure PVDF, and the maximum polarization value is increased from 5.34 μC / cm 2 Increased to 11.79μC / cm 2 , an increase of about 120%, and the residual polarization value increased from 0.98μC / cm 2 Increased to 5.73μC / cm 2 , an increase of about 480%.

[0027] (5) The ferroelectric properties of the sandwich structure composite film of the present invention are compared with the 0-3 type composite film mixed with the same amount of piezoelectric nanoparticles. The maximum polarization value is 5.41μC / cm 2 Increased to 11.79μC / cm 2 , an increase of about 117%, and the residual polarization value increased from 1.45μC / cm 2 Increased to 5.73μC / cm 2 , an increase of about 295%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a flow chart of preparing a sandwich structure flexible piezoelectric composite film according to Example 1;

[0029] Figure 2 is a surface SEM photograph of the sandwich structure flexible piezoelectric composite film prepared in Example 2;

[0030] Figure 3 (a) is a cross-sectional SEM photograph of the sandwich structure flexible piezoelectric composite film prepared in Example 2, and (b) is the result of EDS energy spectrum scanning analysis of the corresponding cross section, where the blue area represents the distribution of Ba element;

[0031] Figure 4 is the piezoelectric coefficient of the samples prepared in Example 1, Example 2 and Comparative Example 1, Comparative Example 2;

[0032] Figure 5 (a) is the hysteresis loop of the sandwich structure flexible piezoelectric composite film prepared in Example 1 and Example 2 and the pure PVDF film prepared in Comparative Example 1; (b) is the hysteresis loop of the sandwich structure flexible piezoelectric composite film prepared in Example 1 and Example 2 and the 0-3 type composite film prepared in Comparative Example 2;

[0033] Figure 6 This is an optical photograph of the sandwich structure flexible composite film prepared in Example 1. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0035] Example 1

[0036] (1) 0.06 g of polyvinylidene fluoride (PVDF) was dissolved in 0.6 mL of N,N-dimethylformamide (DMF) to obtain a 10 wt% PVDF solution, 0.6 mL of the solution was dripped onto a glass substrate using a pipette, and the solution was placed in a vacuum oven at 80° C. for 12 hours and at 160° C. for 6 hours to obtain a PVDF film;

[0037] (2) At room temperature, 3.0 g of barium titanate nanoparticles were added to deionized water and ultrasonically vibrated for 1 hour to make them evenly dispersed; 3.0 g of dopamine hydrochloride powder was added to the system and magnetic stirring was turned on; tris(hydroxymethyl)aminomethane) powder was slowly added to the resulting suspension to control the pH value to 8.5; then the above solution was magnetically stirred for 24 hours, allowed to stand for 1 night, the upper yellow-brown solution was removed with a rubber-tipped dropper, and then washed with deionized water for at least 3 times, and the product was placed in an oven at 80°C for 24 hours to finally obtain BTO@PDA nanoparticles;

[0038] (3) Weigh 5 mg of dopamine-coated barium titanate (BTO@PDA) nanoparticles and disperse them in 10 mL of ethanol solution, and sonicate for at least 30 minutes to obtain a uniformly dispersed suspension;

[0039] (4) placing a PVDF film at the bottom of a beaker, pouring the suspension solution in the above step, and letting it stand for 24 hours until the nanoparticles naturally settle on the film surface to obtain a uniformly distributed nanoparticle layer;

[0040] (5) placing the film in step (4) in a vacuum drying oven and heat treating at 180° C. for 2 hours to obtain a BTO@PDA / PVDF composite film having a double-layer structure;

[0041] (6) placing the composite film prepared in step (5) at the bottom of a beaker with the polymer layer facing upward, pouring the suspension obtained in step (3) into the beaker, and allowing the nanoparticles to naturally settle to the surface of the film for 24 hours to obtain a uniformly distributed nanoparticle layer;

[0042] (7) The film in step (6) was placed in a vacuum drying oven and heat treated at 180° C. for 2 hours to obtain a stable BTO@PDA / PVDF / BTO@PDA piezoelectric composite film with a sandwich structure, wherein the mass ratio of BTO@PDA nanoparticles to PVDF was 1:6. The thickness of the composite film in this embodiment was measured to be 50 μm.

[0043] The preparation process of this embodiment is as follows Figure 1 As shown in the figure, the piezoelectric coefficient d of the sandwich structure flexible piezoelectric composite film prepared in this embodiment is 33 like Figure 4 As shown, the hysteresis loop is Figure 5 The optical photograph of the flexible composite film prepared in this embodiment is shown in Figure 6 shown.

[0044] Example 2

[0045] (1) 0.06 g of polyvinylidene fluoride (PVDF) was dissolved in 0.6 mL of N,N-dimethylformamide (DMF) to obtain a 10 wt% PVDF solution, 0.6 mL of the solution was dripped onto a glass substrate using a pipette, and the solution was placed in a vacuum oven at 80° C. for 12 hours and at 160° C. for 6 hours to obtain a PVDF film;

[0046] (2) At room temperature, 3.0 g of barium titanate nanoparticles were added to deionized water and ultrasonically vibrated for 1 hour to make them evenly dispersed; 3.0 g of dopamine hydrochloride powder was added to the system and magnetic stirring was turned on; tris(hydroxymethyl)aminomethane) powder was slowly added to the resulting suspension to control the pH value to 8.5; then the above solution was magnetically stirred for 24 hours, allowed to stand for 1 night, the upper yellow-brown solution was removed with a rubber-tipped dropper, and then washed with deionized water for at least 3 times, and the product was placed in an oven at 80°C for 24 hours to finally obtain BTO@PDA nanoparticles;

[0047] (3) Weigh 10 mg of dopamine-coated barium titanate (BTO@PDA) nanoparticles and disperse them in 10 mL of ethanol solution, and sonicate for at least 30 minutes to obtain a uniformly dispersed suspension;

[0048] (4) placing a PVDF film at the bottom of a beaker, pouring the suspension solution in the above step, and letting it stand for 24 hours until the nanoparticles naturally settle on the film surface to obtain a uniformly distributed nanoparticle layer;

[0049] (5) placing the film in step (4) in a vacuum drying oven and heat treating at 180° C. for 3 hours to obtain a BTO@PDA / PVDF composite film having a double-layer structure;

[0050] (6) placing the composite film prepared in step (5) at the bottom of a beaker with the polymer layer facing upward, pouring the suspension obtained in step (3) into the beaker, and allowing the nanoparticles to naturally settle to the surface of the film for 24 hours to obtain a uniformly distributed nanoparticle layer;

[0051] (7) The film in step (6) is placed in a vacuum drying oven and heat treated at 180° C. for 3 hours to obtain a stable BTO@PDA / PVDF / BTO@PDA piezoelectric composite film with a sandwich structure, wherein the mass ratio of BTO@PDA nanoparticles to PVDF is 1:3.

[0052] The SEM image of the sandwich structure flexible piezoelectric composite film prepared in this example is as follows: Figure 2 , Figure 3 As shown, Figure 2 The particles evenly distributed on the surface are dopamine-modified BTO nanoparticles with almost no agglomeration. Figure 3 (a) is a cross-sectional SEM image of the composite film with a total thickness of 60 μm. An obvious sandwich structure is observed with a clear interface. The upper and lower BTO@PDA layers are both 5 μm, and the thickness ratio of each layer is 1:10:1. Figure 3 (b) is the result of EDS energy spectrum scanning analysis of the corresponding cross section, and the blue area represents the distribution of Ba element. The piezoelectric coefficient d of the sandwich structure flexible piezoelectric composite film prepared in this embodiment 33 like Figure 4 As shown, the hysteresis loop is Figure 5 shown.

[0053] Comparative Example 1

[0054] (1) 0.06 g of polyvinylidene fluoride (PVDF) was dissolved in 0.6 mL of N,N-dimethylformamide (DMF) to obtain a 10 wt% PVDF solution. 0.2 mL of the solution was dripped onto a glass substrate using a pipette, and the substrate was placed in a vacuum oven and treated at 80°C for 12 hours, 160°C for 6 hours, and 180°C for 3 hours to obtain a PVDF film.

[0055] Comparative Example 2

[0056] (1) Dissolve 0.06 g of polyvinylidene fluoride (PVDF) in 0.6 mL of N,N-dimethylformamide (DMF) to obtain a 10 wt% PVDF solution;

[0057] (2) Weigh 10 mg of dopamine-coated barium titanate (BTO@PDA) nanoparticles and disperse them in the above PVDF solution, and stir them magnetically for 12 h;

[0058] (3) Using a pipette, 0.6 mL of the solution was dripped onto a glass substrate, which was then placed in a vacuum oven and treated at 80° C. for 12 h, 160° C. for 6 h, and 180° C. for 3 h to obtain a 0-3 type structure composite film.

Claims

1. A sandwich structure flexible piezoelectric composite film, characterized in that: The composite film has a sandwich structure, wherein the upper and lower layers are composed of inorganic piezoelectric nanoparticles modified with dopamine, and the middle layer is a polymer film layer; The method for preparing the sandwich structure flexible piezoelectric composite film comprises the following steps: (1) dispersing dopamine-modified inorganic piezoelectric nanoparticles in an ethanol solution to obtain a suspension; (2) placing a polymer film at the bottom of a beaker, pouring the suspension prepared in step (1) into the beaker and allowing the suspension to stand until the nanoparticles naturally settle to a surface of the polymer film, thereby obtaining a nanoparticle layer; (3) heat-treating the polymer film of step (2) to obtain an inorganic nanoparticle layer / polymer film layer having a double-layer structure; (4) placing the inorganic nanoparticle layer / polymer film layer having a double-layer structure in step (3) at the bottom of a beaker with the polymer film layer facing upward, pouring the suspension in step (1) into the beaker and allowing the suspension to stand until the nanoparticles naturally settle to the other surface of the polymer film, thereby obtaining a nanoparticle layer; (5) heat-treating the polymer film of step (4) to obtain a flexible piezoelectric composite film having a sandwich structure; In steps (3) and (5), the heat treatment temperature is 150 to 200° C. and the time is 2 to 3 hours.

2. The sandwich structure flexible piezoelectric composite film according to claim 1, characterized in that: The mass ratio of the inorganic piezoelectric nanoparticles modified with dopamine on the surface in the upper layer or the lower layer to the polymer in the polymer film layer is 1:(1-10), and the thickness of the composite film is 10-100 μm.

3. The sandwich structure flexible piezoelectric composite film according to claim 1, characterized in that: The inorganic piezoelectric nanoparticles are selected from barium titanate (BTO), potassium sodium niobate (KNN) or lead zirconate titanate (PZT) nanoparticles, and have a size of 10 to 100 nm.

4. The sandwich structure flexible piezoelectric composite film according to claim 1, characterized in that: The material of the polymer film layer is selected from PVDF, P (VDF-TrFE), P (VDF-TrFE-CTFE) or PDMS.

5. The sandwich structure flexible piezoelectric composite film according to claim 1, characterized in that: The polymer film is prepared by a casting method or a spin coating method, and has a thickness of 10 to 60 μm.

6. The sandwich structure flexible piezoelectric composite film according to claim 1, characterized in that: The concentration of the suspension is 1-200 mg / mL.

7. An application of the sandwich structure flexible piezoelectric composite film according to any one of claims 1 to 4 in the field of wearable electronic devices or flexible sensing.

Citation Information

Patent Citations

  • One-dimensional metal-doped perovskite-type niobate piezoelectric material, preparation method thereof, flexible piezoelectric film and application thereof

    CN109942022A

  • All-organic metal-free perovskite cement-based piezoelectric material, preparation method and application thereof

    CN111646745A

  • Modified barium titanate hybrid polyvinylidene fluoride copolymer composite membrane and preparation method thereof

    CN108912561A

  • Flexible integrated piezoelectric sensing material and preparation method thereof

    CN110952225A